2009
DOI: 10.1115/1.4000165
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Automatically Optimizing Medical Devices for Treating Heart Failure: Designing Polymeric Injection Patterns

Abstract: Heart failure continues to present a significant medical and economic burden throughout the developed world. Novel treatments involving the injection of polymeric materials into the myocardium of the failing left ventricle (LV) are currently being developed, which may reduce elevated myofiber stresses during the cardiac cycle and act to retard the progression of heart failure. A finite element (FE) simulation-based method was developed in this study that can automatically optimize the injection pattern of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
79
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 21 publications
4
79
0
Order By: Relevance
“…Various volumes of 1, 2, and 4 mL were injected; 2-and 4-mL injections led to superior LVDA and LVSAwith 2-mL injections resulting in significant thickening (despite material degradation) and more pronounced trends for functional improvements. These findings illustrate the importance of injection volume in stabilizing the myocardial wall [67]. Other parameters, such as number and pattern of injections, although relevant through theoretical analysis [67], have yet to be investigated in a clinically relevant model.…”
Section: Materials Optimization: Comparing Properties and Introducing mentioning
confidence: 92%
See 4 more Smart Citations
“…Various volumes of 1, 2, and 4 mL were injected; 2-and 4-mL injections led to superior LVDA and LVSAwith 2-mL injections resulting in significant thickening (despite material degradation) and more pronounced trends for functional improvements. These findings illustrate the importance of injection volume in stabilizing the myocardial wall [67]. Other parameters, such as number and pattern of injections, although relevant through theoretical analysis [67], have yet to be investigated in a clinically relevant model.…”
Section: Materials Optimization: Comparing Properties and Introducing mentioning
confidence: 92%
“…Theoretical models have implied that material properties, specifically mechanics and volume, are important to consider when selecting the type of bulking agent to ameliorate dilation and increased stress in the myocardial wall [35,[65][66][67]. Using a finite element (FE) model to simulate the effects of injecting a non-contractile material into the myocardium, Wall et al showed that bulking the myocardium was sufficient to attenuate post-MI geometric changes and, thus, decrease stress in the myocardial wall [35].…”
Section: Materials Optimization: Theoretical Evaluationmentioning
confidence: 99%
See 3 more Smart Citations